Black-Jewish relations on trial : Leo Frank and Jim Conley in the new South - Melnick, Jeffrey Paul (University Press of Mississippi, 2000)
An analysis of the Leo Frank case as a measure of the complexities characterizing the relationship between African Americans and Jews in America In 1915 Leo Frank, a Northern Jew, was lynched in Georgia. He had been convicted of the murder of Mary Phagan, a young white woman who worked in the Atlanta pencil factory managed by Frank. In a tumultuous trial in 1913 Frank's main accuser was Jim Conley, an African American employee in the factory. Was Frank guilty? In our time a martyr's aura falls over Frank as a victim of religious and regional bigotry. The unending controversy has inspired debat.